2021
DOI: 10.1038/s41598-021-97887-z
|View full text |Cite
|
Sign up to set email alerts
|

A combination approach of pseudotime analysis and mathematical modeling for understanding drug-resistant mechanisms

Abstract: Cancer cells acquire drug resistance through the following stages: nonresistant, pre-resistant, and resistant. Although the molecular mechanism of drug resistance is well investigated, the process of drug resistance acquisition remains largely unknown. Here we elucidate the molecular mechanisms underlying the process of drug resistance acquisition by sequential analysis of gene expression patterns in tamoxifen-treated breast cancer cells. Single-cell RNA-sequencing indicates that tamoxifen-resistant cells can … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Single-cell RNA sequencing (scRNA-seq) was performed on h-iSCs and h-MSCs using the ICELL8 System as described 27 by a contract service (Takara Bio, Inc., Shiga, Japan). The resulting data were further analyzed using Surate 4.2.…”
Section: Methodsmentioning
confidence: 99%
“…Single-cell RNA sequencing (scRNA-seq) was performed on h-iSCs and h-MSCs using the ICELL8 System as described 27 by a contract service (Takara Bio, Inc., Shiga, Japan). The resulting data were further analyzed using Surate 4.2.…”
Section: Methodsmentioning
confidence: 99%
“…To understand transcriptional regulation during drug resistance acquisition, we analyzed a published dataset containing time-series scRNA-seq data of MCF-7 cells subjected to continuous tamoxifen treatment [11]. The data were collected at weeks 0 (before tamoxifen treatment), 3, 6, and 9, referred to as W0, W3, W6, and W9, respectively ( Figure 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…We noticed that the population ratio in the G2/M phase drastically decreased from C1 to C2 but gradually increased from C2 to C4 ( Figure 2e , right). Since tamoxifen treatment induces G1 arrest followed by gradual cell growth recovery [11], we assumed that the C1-C2-C3-C4 axis approximately corresponds to the progression of tamoxifen resistance acquisition, whereas C5 predominantly consists of cells in S and G2/M phases.…”
Section: Resultsmentioning
confidence: 99%
“…To understand transcriptional regulation dynamics underlying drug resistance acquisition, we analyzed a published dataset containing time-series scRNA-seq data of MCF-7 cells subjected to continuous tamoxifen treatment [11]. The data were collected at weeks 0 (before tamoxifen treatment), 3, 6, and 9, referred to as W0, W3, W6, and W9, respectively (Figure 2a).…”
Section: Dissecting the Heterogeneity And Defining Pseudotime For Mcf...mentioning
confidence: 99%
“…These studies investigated the activation of cell survival signals, such as the NF-κB pathway. Furthermore, Magi et al reported altered metabolic regulation, cell adhesion, and histone modification based on the analysis of time-series scRNA-seq data under tamoxifen treatment [11]. While these studies have uncovered important genes and pathways associated with drug resistance acquisition, gaps still exist in our understanding of regulatory mechanisms at the systems level.…”
Section: Introductionmentioning
confidence: 99%